2022
DOI: 10.1038/s41598-022-09897-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 spike IgG antibodies after the second BNT162b2 mRNA vaccine in Japanese kidney transplant recipients

Abstract: We aimed to evaluate the seroprevalence and investigated factors associated with seropositivity after the second SARS-CoV-2 mRNA vaccination in kidney transplant (KT) recipients. This retrospective study conducted between June and November 2021 included 106 KT recipients and 127 healthy controls who received the second dose of the BNT162b2 mRNA vaccine at least 7 days before the measurement of antibody titers. The antibody titer against the receptor-binding domain of SARS-CoV-2 spike (S) protein was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Murhekar and colleagues [37] reported seroprevalence rates of 81% and 89.8% among adults who had received one dose and 2 doses of COVID-19 vaccines respectively. Similarly, Hamaya et al [43] reported seroprevalence rate of 98% among healthy adults after the second dose of the BNT162b2 mRNA vaccine. Our study is in tandem with these previous studies as 69.2% and 73.8% seroprevalence rates were observed post first and second doses of COVID-19 vaccine respectively.…”
Section: Plos Onementioning
confidence: 86%
See 1 more Smart Citation
“…Murhekar and colleagues [37] reported seroprevalence rates of 81% and 89.8% among adults who had received one dose and 2 doses of COVID-19 vaccines respectively. Similarly, Hamaya et al [43] reported seroprevalence rate of 98% among healthy adults after the second dose of the BNT162b2 mRNA vaccine. Our study is in tandem with these previous studies as 69.2% and 73.8% seroprevalence rates were observed post first and second doses of COVID-19 vaccine respectively.…”
Section: Plos Onementioning
confidence: 86%
“…Similarly, Hamaya et al . [ 43 ] reported seroprevalence rate of 98% among healthy adults after the second dose of the BNT162b2 mRNA vaccine. Our study is in tandem with these previous studies as 69.2% and 73.8% seroprevalence rates were observed post first and second doses of COVID-19 vaccine respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They reported antibody titers were not significantly deteriorated in patients with steroid treatment for immune-related adverse events. Moreover, organ transplant recipients receiving multidrug immunosuppressive therapy are known to have significantly suppressed immune responses to mRNA vaccines [ 13 , 19 ]. It is reported that not the dose alone but the cumulative dose is considered important for estimating the risk of infection from steroids (the risk associated with 5mg prednisolone taken for the last 3 years was similar to that associated with 30 mg taken for a month) [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples for regular examination were cross-sectionally obtained. The titers of the immunoglobulin G (IgG) antibodies against the SARS-CoV-2 spike (S) receptor-binding domain were determined using the Elecsys anti-SARS-CoV-2 S RUO (Covas 8000/e 801; Roche-Diagnostics, Mélan, France) as described previously [ 13 , 14 ]. We used IgG titers of 15 U/mL or more, which is sufficient for the presence of neutralizing antibodies, as a cutoff value in this study.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid multi-collinearity, only variables with VIF<10 were included in multivariate analysis. A multivariate logistic regression model was built to analyze risk factors of BTI, adjusting for age, kidney graft function and mycophenolate mofetil use, considered as important variables influencing immune responses to SARS-CoV-2 vaccination, based on our linear regression data and on published data (30, 31) . Missing data were excluded from the final analysis.…”
Section: Methodsmentioning
confidence: 99%